DINAMIKA PENERIMAAN DIRI ORANG TUA YANG MENIKAHKAN ANAKNYA DENGAN PELAKU KEKERASAN SEKSUAL (STUDI KASUS DI KELURAHAN MAHAKERET TIMUR) - Halid, Eliana; Solang, Deetje J.; Naharia, Melkian (PSIKOPEDIA, 2025)
The purpose of this study is to determine and describe the dynamics of parental acceptance of marrying off their children to people who commit sexual violence against their children. This research method uses a qualitative research approach with a phenomenological study. The implementation of the research will be carried out sequentially and structured. It will be carried out within a period of 1-2 months. Located at the subject's residence in Mahakeret Timur Village, Wenang District, Manado City. The data collection technique will use research instruments. The research instruments are considered appropriate to the needs of this study, including observation, interviews, and documentation. Based on the results of the research analysis of the two research subjects. Subject Ros showed a good sense of equality. Because through the observations obtained, subject Ros actively socializes and almost never disagrees with anyone, which is a very good ability considering the location where the subject lives, namely Mahakeret, showing a sense of equality is one aspect of self-acceptance. Subject Ros and Edy both agree that the concept of both of them is that they have fulfilled their responsibilities towards their children, namely sending their children to school until they complete 12 years of compulsory education, even though in the end they marry young, as parents they feel they have fulfilled their responsibilities.